Meaningful Brands from Meaningless Differentiation: The Dependence on Irrelevant Attributes - Carpenter, Gregory S.; Glazer, Rashi; Nakamoto, Kent (Journal of Marketing Research, 1994)
Conventional product differentiation strategies prescribe distinguishing a product or brand from competitors’ on the basis of an attribute that is relevant, meaningful, and valuable to consumers. However, brands also successfully differentiate on an attribute that appears to create a meaningful product difference but on closer examination is irrelevant to creating that benefit—“meaningless” differentiation. The authors examine how meaningless differentiation can produce a meaningfully differentiated brand. They argue that buyers may infer that a distinguishing but irrelevant attribute is in fact relevant and valuable under certain conditions, creating a meaningfully differentiated brand. They outline the consumer inference process and develop a set of hypotheses about when it will produce meaningful brands from meaningless differentiation. Experimental tests in three product categories support their analysis. They explore the implications of the results for product differentiation strategies, consumer preference formation, and the nature of competition.